Mengembangkan Kecerdasan Spiritual Anak Melalui Kegiatan Tahfidzul Qur’an di LKSA Ridha Muhammadiyah Enrekang - Aisyah Suryani; Achmad Dahlan Muchtar; Lisa Lisa; Kairawan Kairawan (Universitas Muhammadiyah Enrekang, 2022)
Spiritual intelligence is intelligence that is in a person's self that is related to wisdom beyond the ego or human conscious mind. To determine the level of spiritual intelligence cannot be seen easily because spiritual intelligence is a skill that is personal and related to the creator. With the Tahfidzul Qur'an activity it is hoped that it will be able to develop the spiritual intelligence of orphanage children so that they have a strong faith. This research was conducted to determine the implementation of Tahfidzul Qur'an activities at LKSA Ridha Muhammadiyah Enrekang and to determine the impact of Tahfidzul Qur'an activities on the spiritual intelligence of children at LKSA Ridha Muhammadiyah Enrekang. This study used a qualitative approach with data collection techniques in the form of interviews, observation and documentation. Data analysis techniques include data reduction, data display, and drawing conclusions. The results found were firstly using the classical class of the Fahmul Mahfudz method, namely before the verses were memorized, secondly, using the sorogan method, namely transferring the memorization to the ustadz directly by submitting it to the teacher as ta'dim, thirdly, using the Muroja'ah method, namely repeating the memorization that had been memorized. memorized or refresh the memorization every day continuously and istiqomah. With the three methods applied, it can indirectly develop children's spiritual intelligence.